A crosstalk between autophagy and apoptosis in intracerebral hemorrhage - Wang, Moyan; Chen, Xin; Li, Shuangyang; Wang, Lingxue; Tang, Hongmei; Pu, Yuting; Zhang, Dechou; Fang, Bangjiang; Bai, Xue (Frontiers in Cellular Neuroscience, 2024)
Intracerebral hemorrhage (ICH) is a severe condition that devastatingly harms human health and poses a financial burden on families and society. Bcl-2 Associated X-protein (Bax) and B-cell lymphoma 2 (Bcl-2) are two classic apoptotic markers post-ICH. Beclin 1 offers a competitive architecture with that of Bax, both playing a vital role in autophagy. However, the interaction between Beclin 1 and Bcl-2/Bax has not been conjunctively analyzed. This review aims to examine the crosstalk between autophagy and apoptosis in ICH by focusing on the interaction and balance of Beclin 1, Bax and Bcl-2. We also explored the therapeutic potential of Western conventional medicine and traditional Chinese medicine (TCM) in ICH via controlling the crosstalk between autophagy and apoptosis.